A study of the teratogenicity of diphenylhydantoin and phenobarbitone in the experimental mouse - Beyers, Nulda (Division of Clinical Pharmacology, 2017)
The aims of the research were to establish whether diphenylhydantoin and phenobarbitone are teratogenic in mice both in vivo and in an in vitro whole embryo culture system, to investigate possible mechanisms of teratogenicity and to examine whether the methods used in this study, may form a basis for developing systems of more extensive drug teratogenicity screening.